2015
DOI: 10.1186/s12967-015-0464-6
|View full text |Cite
|
Sign up to set email alerts
|

FH535 increases the radiosensitivity and reverses epithelial-to-mesenchymal transition of radioresistant esophageal cancer cell line KYSE-150R

Abstract: BackgroundAcquired radioresistance has significantly compromised the efficacy of radiotherapy for esophageal cancer. The purpose of this study is to investigate the roles of epithelial-mesenchymal transition (EMT) and the Wnt/β-catenin signaling pathway in the acquirement of radioresistance during the radiation treatment of esophageal cancer.MethodsWe previously established a radioresistant cell line (KYSE-150R) from the KYSE-150 cell line (a human cell line model for esophageal squamous cell carcinoma) with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
(26 reference statements)
3
40
0
Order By: Relevance
“…Preliminary evidence indicates that Wnt/β-catenin signaling may trigger epithelial to mesenchymal transition (EMT), which has been implicated in increased resistance to radiotherapy (28,3538). In our gene expression data, we observed an overexpression of genes associated with EMT in resistant cell populations, underscoring the importance of the Wnt/β-catenin EMT axis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence indicates that Wnt/β-catenin signaling may trigger epithelial to mesenchymal transition (EMT), which has been implicated in increased resistance to radiotherapy (28,3538). In our gene expression data, we observed an overexpression of genes associated with EMT in resistant cell populations, underscoring the importance of the Wnt/β-catenin EMT axis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of NEAT1 could sensitize NPC cells to radiation in vitro . NEAT1 may also induce EMT phenotype, which is a key contributor to radioresistance [84]. In addition, there was a physical interaction between NEAT1 and miR-204 in NPC cells.…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…A number of studies have confirmed that radiation can induce EMT or phenotypic changes similar to EMT (7375). For example, in KYSE-150R cells, a radioresistant esophageal cancer cell line, phenotypic changes similar to EMT are induced by radiation, including decreased E-cadherin and increased Snail and Twist expressions (76), which are also observed in nasopharyngeal carcinoma (77) and colorectal cancer (78). Furthermore, a number of pathways have been reported to contribute to radiation-induced EMT of cancer cells.…”
Section: Radiation Induces Emt In Cancermentioning
confidence: 99%